A method for preparing a methanol synthesis catalyst based on a copper-zinc loaded matrix
A copper-zinc composite catalyst was prepared by coating zinc particles onto the surface of copper particles using a stepwise in-situ precipitation method and combining it with an aluminum gel carrier. This solved the problem of uneven distribution of copper and zinc active components and improved the utilization rate of active sites and catalytic activity of the catalyst.
Patent Information
- Application Number
- CN202111391476.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-11-23
AI Technical Summary
The uneven distribution of copper and zinc active components in existing Cu-ZnO-Al2O3 catalysts leads to the waste of bulk catalytic active sites and low utilization rate of catalytic active sites. Traditional co-precipitation methods are difficult to form uniform and stable copper-zinc coated particles, which affects catalytic activity.
A stepwise in-situ precipitation method was used to partially coat zinc particles onto the surface of copper particles. Aluminum glue was then added as a catalyst carrier. The copper-zinc composite parent catalyst was prepared by washing, drying, calcining, molding, and reduction.
This method achieves uniform and stable zinc coating on the copper surface, reduces the waste of bulk catalytic active sites, improves the overall utilization rate of catalytic active sites in the catalyst, and enhances catalytic activity.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and relates to a method for preparing a methanol synthesis catalyst based on a copper-zinc loaded matrix. Background Art
[0002] Methanol (CH3OH) is the simplest saturated monohydric alcohol. It is a colorless liquid at room temperature and pressure. It is volatile, flammable, and has a slightly mellow odor. It is completely miscible with water and is easily soluble in alcohol ethers and most other organic solvents. In addition, methanol has methyl and hydroxyl groups in its structure and is chemically active. It can undergo oxidation, condensation, dehydration, methylation and other reactions ( Prog. Energy Combust. Sci ., 2016, 56 , 71-105). Therefore, methanol can not only be used as a solvent and auxiliary agent in various chemical reactions, but also as a reaction raw material to produce acetaldehyde, ethanol, ethylene glycol, methyl tert-butyl ether, methyl acrolein, etc. In recent years, methanol has also been favored at home and abroad as an environmentally friendly energy source and a fuel with great potential.
[0003] Currently, the most widely used methanol synthesis catalyst in industry is mainly Cu-ZnO-Al2O3 catalyst, in which Cu-ZnO is the synergistic active component of the catalyst, and Al2O3 serves as a carrier to provide support for the active components of the catalyst. The most commonly used method for synthesizing Cu-ZnO-Al2O3 catalyst is the co-precipitation method. The copper and zinc active components of the catalyst obtained by this method are distributed both on the surface of the catalyst and in the bulk of the catalyst. In previous studies, scientists often control the various process parameters of the co-precipitation method to improve the uniformity of the copper and zinc components in order to achieve the purpose of regulating the catalytic activity and catalytic life of the catalyst ( Catalysts , 2015, 5 , 145-269). However, due to the limited internal pores of oxide catalysts, this type of catalyst is mostly surface catalytic, and the catalytic process occurring in the bulk phase is relatively rare, which undoubtedly causes a certain waste of bulk copper and zinc active sites formed inside the catalyst. Under this premise, blindly pursuing the uniform distribution of Cu and ZnO in the overall structure of the catalyst is not conducive to improving the utilization rate of the catalyst active sites.
[0004] In addition, studies have shown that the active sites of the Cu-ZnO-Al2O3 catalyst are located at the interface formed by ZnO coating on the surface of Cu particles ( Science , 2016, 352 , 969-974). The formation of this active site not only provides strong reaction activity, but also ZnO particles can space and stabilize copper particles, slow down their thermal migration and agglomeration tendency, and increase the thermal stability of the catalyst ( Angew. Chem. Int. Ed. , 2007,46 , 7324-7327). However, the traditional co-precipitation method is difficult to ensure the formation of uniform and stable copper-zinc coated particles, which affects the catalytic activity and active site utilization of the catalyst to a certain extent. Summary of the invention
[0005] 1. Technical problems to be solved:
[0006] The active component of zinc oxide coated on the copper surface is formed uniformly and stably on the catalyst, the waste caused by the formation of bulk catalytic active sites is reduced, and the utilization rate of the overall catalytic active sites of the catalyst is further improved.
[0007] 2. Technical solution:
[0008] The present invention provides a method for preparing a methanol synthesis catalyst based on a copper-zinc loaded matrix, which breaks through the technical bias of improving the catalytic activity by increasing the dispersion of the catalyst in the traditional method. Through this method, an active component of zinc oxide coated uniformly and stably on the copper surface is formed, the waste caused by the formation of bulk catalytic active sites is reduced, and the utilization rate of the overall catalytic active sites of the catalyst is further improved.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A copper-zinc composite matrix in which zinc particles are partially coated on the surface of copper particles is prepared by a step-by-step in-situ precipitation method, and then aluminum gel is added as a catalyst carrier. Finally, a methanol synthesis catalyst is obtained through washing, drying, calcining, molding, and reduction processes. The preparation method of the catalyst comprises the following steps:
[0011] (1) A copper matrix is prepared by using a copper salt solution and an alkaline precipitant, and then a zinc salt solution and an alkaline precipitant are added in situ to the copper matrix suspension to prepare a copper-zinc composite matrix in which zinc particles are partially coated on the surface of the copper particles.
[0012] Preferably, the alkaline precipitant is one or more of NaOH, NH3·H2O, NaHCO3, and Na2CO3.
[0013] Preferably, the conditions for the neutralization operation are precipitation pH 7-9 and precipitation temperature 40-90 °C.
[0014] Preferably, the molar ratio of copper to zinc in the copper salt solution and the zinc salt solution is 1:1-5:1.
[0015] (2) After washing, the mixture is added to the pre-synthesized aluminum gel for mixing and slurrying.
[0016] Preferably, the preparation method of the aluminum gel is: an aqueous solution of aluminum nitrate and an aqueous solution of an alkaline precipitant are subjected to a neutralization reaction, characterized in that the precipitation pH is 7-9 and the precipitation temperature is 30-80 °C.
[0017] Preferably, the ratio of the total molar amount of copper and zinc to the molar amount of aluminum is 5:1-10:1.
[0018] (3) After washing, drying, calcining, molding and reduction steps, the target methanol synthesis catalyst is obtained.
[0019] Preferably, the sample is dried at 80-120 °C for 6-12 hours.
[0020] Preferably, the sample is calcined at 300-400 °C in air atmosphere for 30-60 minutes.
[0021] Preferably, the molding conditions of the sample are: 2-6 wt% graphite is added to the solid to facilitate demolding and tableting.
[0022] 3. Beneficial effects:
[0023] The present invention provides a method for preparing a methanol synthesis catalyst based on a copper-zinc loaded matrix, wherein a copper-zinc composite matrix partially coating zinc particles on the surface of copper particles is prepared by a step-by-step in-situ precipitation method, and then aluminum gel is added as a catalyst carrier, and finally a methanol synthesis catalyst is obtained after drying, washing, roasting, forming, and reduction processes. Through this method, a convenient method is used to obtain an active component that uniformly and stably coats zinc oxide on the surface of copper, and an efficient methanol synthesis catalyst is obtained based on the active component. This local distribution mode of the copper-zinc active component can reduce the waste caused by the formation of bulk catalytic active sites and further improve the overall catalytic active site utilization of the catalyst. The present invention breaks through the technical prejudice of effectively improving the catalytic activity by increasing the dispersion of the catalyst in the traditional method. DETAILED DESCRIPTION
[0024] The following specific examples are only used to further illustrate the technical solutions of the present invention in detail, and the effects of the methods of the present invention are not limited thereto.
[0025] Example 1
[0026] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0027] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 °C for 6 hours.
[0028] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0029] Example 2
[0030] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of Na2CO3 aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of Na2CO3 aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0031] 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and 1 mol / L Na2CO3 aqueous solution were added to the continuous neutralization reactor through a metering pump at the same time, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and the slurry was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours.
[0032] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0033] Example 3
[0034] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was maintained at 90 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 9.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 90 ° C and the neutralization pH of 9.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0035] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 °C for 6 hours.
[0036] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0037] Example 4
[0038] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was maintained at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 29.7 g of zinc nitrate hexahydrate and 1 mol / L NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0039] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 40 °C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 °C for 6 hours.
[0040] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0041] Example 5
[0042] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0043] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 80 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 9.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours.
[0044] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0045] Example 6
[0046] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0047] 1 L aqueous solution containing 37.5 g aluminum nitrate nonahydrate and 1 mol / L NaOH aqueous solution were added to the continuous neutralization reactor through a metering pump at the same time, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours.
[0048] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0049] Example 7
[0050] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 120 ° C for 12 hours for use.
[0051] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 120 °C for 12 hours.
[0052] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0053] Example 8
[0054] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0055] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 °C for 6 hours.
[0056] The solid was calcined in a muffle furnace at 400 °C in air atmosphere for 60 minutes. After 60 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and broken into 16-40 mesh.
[0057] Example 9
[0058] 1 L aqueous solution containing 120.8 g of copper nitrate trihydrate and 1 mol / L of NaOH aqueous solution were added to the continuous neutralization reactor by a metering pump at the same time, the temperature was kept at 40 ° C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the copper matrix reaction was completed, 1 L aqueous solution containing 148.7 g of zinc nitrate hexahydrate and 1 mol / L of NaOH aqueous solution were added to the obtained suspension by a metering pump in situ for neutralization, and the reaction temperature of 40 ° C and the neutralization pH of 7.0 were still maintained. After the step-by-step neutralization was completed, the mixture was filtered, washed, and dried in an oven at 80 ° C for 6 hours for use.
[0059] A 1 L aqueous solution containing 75.0 g of aluminum nitrate nonahydrate and a 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 7.0. After neutralization, the prepared copper-zinc loaded matrix was added and slurrying was continued for 30 minutes. Finally, the mixture was filtered, washed, and dried in an oven at 80 °C for 6 hours.
[0060] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 6 wt% of graphite was added, and then demolded and broken into 16-40 mesh.
[0061] Comparative Example
[0062] 1 L aqueous solution containing 148.7 g zinc nitrate hexahydrate, 120.8 g copper nitrate trihydrate, and 75.0 g aluminum nitrate nonahydrate and 1 mol / L NaOH aqueous solution were added to the continuous neutralization reactor through a metering pump at the same time, and the temperature was maintained at 40°C and the pH of the solution in the continuous neutralization reactor was controlled to be 7.0. After the reaction was completed, the mixture was filtered, washed, and dried in an oven at 80°C for 6 hours before use.
[0063] The solid was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes. After 30 minutes, the solid was taken out and weighed, and 2 wt% of graphite was added, and then demolded and crushed into 16-40 mesh.
[0064] Activity test conditions: The copper-zinc-supported methanol synthesis catalyst was used to prepare methanol from syngas, and the activity of the catalyst was evaluated in a micro-fixed bed continuous flow reactor. The catalyst loading was 4 mL, and the sample was heated in a H2 / N2 mixed gas containing 5% H2 at 20 °C h under normal pressure before the reaction. -1 The temperature was programmed to rise to 230°C for 10 h for reduction treatment. Subsequently, the catalyst was heated in a syngas atmosphere with the following composition: CO (13–15%), CO2 (3–5%), H2 (55–65%), and the remainder N2 at a space velocity of 10000 h -1 The methanol synthesis catalytic reaction was carried out under the conditions of 37°C, 50°C reaction pressure and 230°C reaction temperature.
[0065] Taking Example 1, Example 4 and the comparative example as examples, the activity evaluation results are shown in the table:
[0066] catalyst Example 1 Example 4 Comparative Example Methanol yield [g / (mL-Cat·h)] 1.52 1.56 1.37 Methanol selectivity (%) 97.5 97.7 97.0
[0067] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.
Claims
1. Application of a methanol synthesis catalyst based on a copper-zinc composite matrix in preparing methanol from synthesis gas, characterized in that: The preparation method of the methanol synthesis catalyst comprises the following steps: (1) preparing a copper matrix suspension using a copper salt solution and an alkaline precipitant; (2) adding a zinc salt solution and an alkaline precipitant in situ into the copper matrix suspension to prepare a copper-zinc composite matrix in which zinc particles are partially coated on the surface of copper particles; (3) washing the copper-zinc composite matrix and adding it to pre-synthesized aluminum colloid for mixing and slurrying; (4) obtaining a target methanol synthesis catalyst after washing, drying, calcining, molding and reducing steps; The alkaline precipitant in steps (1) and (2) is one or more of NaOH, NH3·H2O, NaHCO3, and Na2CO3. In steps (1) and (2), the neutralization precipitation pH is 7–9, the precipitation temperature is 40–90°C, and the molar ratio of copper to zinc in step (2) is 1:1–5:1; In step (3), the ratio of the total molar amount of copper and zinc to the molar amount of aluminum is 5:1-10:
1. The preparation method of aluminum gel in step (3) is: neutralizing an aqueous solution of aluminum nitrate with an aqueous solution of an alkaline precipitant, the precipitation pH is 7-9, and the precipitation temperature is 30-80°C; The calcination process in step (4) is carried out under the conditions of 300-400°C in air atmosphere for 30-60 minutes.
2. The use according to claim 1, characterized in that The drying process in step (4) is carried out under the conditions of 80-120°C for 6-12 hours.
3. The use according to claim 1, characterized in that: The molding process in step (4) is to add 2-6 wt% graphite to the solid.
Citation Information
Patent Citations
Preparation method of copper-zinc catalyst
CN107790137A